Outcomes in Temporary ICUs Versus Conventional ICUs: An Observational Cohort of Mechanically Ventilated Patients With COVID-19-Induced Acute Respiratory Distress Syndrome - Jimenez, Jose Victor; Olivas-Martinez, Antonio; Rios-Olais, Fausto Alfredo; Ayala-Aguillón, Frida; Gil- López, Fernando; Leal-Villarreal, Mario Andrés de Jesús; Rodríguez-Crespo, Juan José; Jasso-Molina, Juan C.; Enamorado-Cerna, Linda; Dardón-Fierro, Francisco Eduardo; Martínez-Guerra, Bernardo A.; Román-Montes, Carla Marina; et al. (Critical care explorations, 2022)
IMPORTANCE: Throughout the COVID-19 pandemic, thousands of temporary ICUs have been established worldwide. The outcomes and management of mechanically ventilated patients in these areas remain unknown. OBJECTIVES: To investigate mortality and management of mechanically ventilated patients in temporary ICUs. DESIGN, SETTING, AND PARTICIPANTS: Observational cohort study in a single-institution academic center. We included all adult patients with severe COVID-19 hospitalized in temporary and conventional ICUs for invasive mechanical ventilation due to acute respiratory distress syndrome from March 23, 2020, to April 5, 2021. MAIN OUTCOMES AND MEASURES: To determine if management in temporary ICUs increased 30-day in-hospital mortality compared with conventional ICUs. Ventilator-free days, ICU-free days (both at 28 d), hospital length of stay, and ICU readmission were also assessed. RESULTS: We included 776 patients (326 conventional and 450 temporary ICUs). Thirty-day in-hospital unadjusted mortality (28.8% conventional vs 36.0% temporary, log-rank test p = 0.023) was higher in temporary ICUs. After controlling for potential confounders, hospitalization in temporary ICUs was an independent risk factor associated with mortality (hazard ratio, 1.4; CI, 1.06-1.83; p = 0.016).There were no differences in ICU-free days at 28 days (6; IQR, 0-16 vs 2; IQR, 0-15; p = 0.5) or ventilator-free days at 28 days (8; IQR, 0-16 vs 5; IQR, 0-15; p = 0.6). We observed higher reintubation (18% vs 12%; p = 0.029) and readmission (5% vs 1.6%; p = 0.004) rates in conventional ICUs despite higher use of postextubation noninvasive mechanical ventilation (13% vs 8%; p = 0.025). Use of lung-protective ventilation (87% vs 85%; p = 0.5), prone positioning (76% vs 79%; p = 0.4), neuromuscular blockade (96% vs 98%; p = 0.4), and COVID-19 pharmacologic treatment was similar. CONCLUSIONS AND RELEVANCE: We observed a higher 30-day in-hospital mortality in temporary ICUs. Although both areas had high adherence to evidence-based management, hospitalization in temporary ICUs was an independent risk factor associated with mortality.